Mechanical Milling Behavior of Pure Magnesium Powder - Koo, Seoung Mo; Kim, Gyung-ho; Hwang, Dae Youn; Kim, Hye Sung (KOREAN INST METALS MATERIALS, 2015)
The microstructural evolution and mechanical properties during mechanical milling of pure magnesium powders were investigated as a function of the milling time and processing control agent. Commercially pure magnesium powders were mechanically milled in a SPEX 8000 shaker Mixer/Mill in an inert atmosphere. From the TEM observations and the analysis of the X-ray diffraction patterns, the steady state grain size was approximately 75 nm regardless of the addition of a processing control agent, while the milling time to reach steady state was shorter when a processing control agent (1wt% stearic acid) was added to the pure magnesium. It is noteworthy that the steady state hardness of the pure magnesium with the processing control agent was hardly different from that of the pure magnesium milled without PCA. Hence, we conclude that the oxides present in the magnesium surface function the same as that of the PCA, and their effectiveness is dependent on the characteristics of the magnesium surface oxides broken by mechanical milling.
Keywords: NANOCRYSTALLINE METALS; GRAIN-SIZE